Redesign Planning of B3 Waste Temporary Storage Site (TPS) of PT X Located in Pasuruan Industrial Estate Rembang (PIER): Redesain Tempat Penyimpanan Sementara (TPS) Limbah B3 PT X di Pasuruan Industrial Estate Rembang (PIER) - Ahmad Baihaqi Yudhistira; Muhammad Abdus Salam Jawwad (Envirous, 2025)
PT X is a company that runs in the business of industry and trade in pharmaceutical products, as well as laboratory testing services in the animal feed sector. In the future, PT X plans to open laboratory testing services in the animal feed sector, so the condition of PT X's B3 Waste Temporary Storage Site (TPS) needs to be redesigned to comply with applicable regulations. Therefore, it is necessary to redesign the company's B3 Waste TPS building to comply with PP No. 22 of 2021 and PermenLHK No. 6 of 2021. This journal is aimed at redesigning PT X’s B3 waste temporary storage site so that it meets the established regulations and improves B3 waste storage activities at PT X. This research journal begins with collecting data, type, and characteristics of hazardous waste. Based on data on the amount of B3 Waste output, the storage capacity of the B3 Waste TPS at PT X can be said to still not be in accordance with applicable regulations. The results of the journal, PT X’s TPS able to store the planned waste and in accordance with established regulations.